Clinical Efficacy of Intravenous Papaverine plus Ketorolac in the Emergency Treatment of Renal Colic: A Letter to the Editor - Mahboube Neamatshahi; Aghilallah Keykhosravi (Iranian Journal of Medical Sciences)
We recently have read with great interest an article entitled “Clinical Efficacy of Intravenous Papaverine plus Ketorolac in the Emergency Treatment of Renal Colic: A Randomized, Double-blind Clinical Trial”, by Mohammadreza Pirouzi and colleagues, which was published in your esteemed journal (Vol 49, No. 11, November 2024).